POLITIK INSTITUSI REZIM INTERNASIONAL (KONSEP DAN PENDEKATAN ANALISIS) - Rendi Prayuda; Syafri Harto (Journal of Diplomacy and International Studies, 2019)
The concept of international anarchy initially clarifies the absence of actors in international politics of the supernatural organization in the practice of international relations. But the existence of international regime in international politics currently affects the pattern of relations between countries in creating and facilitating the creation and international cooperation. This article analyzes the concepts and approaches of international regime studies by using a qualitative, descriptive approach conducted by a literature study method. The results of this study show that the international regime is the specific actualisation of international organisations formed in a centralistic, independent and rationality. An analysis approach to the international regime is carried out with a rationalist and reflectiveal approach.